Evaluation of low-level laser therapy effectiveness on the pain and masticatory performance of patients with myofascial pain - de Moraes Maia, Mila Leite; Ribeiro, Maria Amália Gonzaga; Maia, Luiz Guilherme Martins [UNESP]; Stuginski-Barbosa, Juliana; Costa, Yuri Martins; Porporatti, André Luís; Conti, Paulo César Rodrigues; Bonjardim, Leonardo Rigoldi (Springer Nature, 2012)
This study investigated the effect of low-level laser therapy (LLLT) on the masticatory performance (MP), pressure pain threshold (PPT), and pain intensity in patients with myofascial pain. Twenty-one subjects, with myofascial pain according to Research Diagnostic Criteria/temporomandibular dysfunction, were divided into laser group (n = 12) and placebo group (n = 9) to receive laser therapy (active or placebo) two times per week for 4 weeks. The measured variables were: (1) MP by analysis of the geometric mean diameter (GMD) of the chewed particles using Optocal test material, (2) PPT by a pressure algometer, and (3) pain intensity by the visual analog scale (VAS). Measurements of MP and PPT were obtained at three time points: baseline, at the end of treatment with low-level laser and 30 days after (follow-up). VAS was measured at the same times as above and weekly throughout the laser therapy. The Friedman test was used at a significance level of 5 % for data analysis. The study was approved by the Ethics Committee of the Federal University of Sergipe (CAAE: 0025.0.107.000-10). A reduction in the GMD of crushed particles (p < 0.01) and an increase in PPT (p < 0.05) were seen only in the laser group when comparing the baseline and end-of-treatment values. Both groups showed a decrease in pain intensity at the end of treatment. LLLT promoted an improvement in MP and PPT of the masticatory muscles. © 2012 Springer-Verlag London.
Keywords: Laser therapy; Masticatory performance; Myofascial pain; Pressure pain threshold; Temporomandibular dysfunction